2003
DOI: 10.1016/s0042-6822(03)00400-8
|View full text |Cite
|
Sign up to set email alerts
|

Control of HIV-1 env RNA splicing and transport: investigating the role of hnRNP A1 in exon splicing silencer (ESS3a) function

Abstract: The control of HIV-1 viral RNA splicing and transport plays an important role in the successful replication of the virus. Previous studies have identified both an exon splicing enhancer (ESE) and a bipartite exon splicing silencer (ESS3a and ESS3b) within the terminal exon of HIV-1 that are involved in modulating both splicing and Rev-mediated export of viral RNA. To define the mechanism of ESS3a function, experiments were carried out to better define the cis and trans components required for ESS3a activity. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 51 publications
0
30
0
Order By: Relevance
“…Previously, we demonstrated that the ESS3 within the terminal exon of HIV-1 not only inhibits use of the adjacent 3Ј ss but also blocks Rev-mediated export of the unspliced viral RNA to the cytoplasm (Pongoski et al 2002;Asai et al 2003). This block to Rev-mediated export was not due solely to the inhibition of splicing because replacement of ESS3 with high affinity hnRNP A1-binding sites was found to yield a comparable reduction in splicing but did not inhibit RNA transport (Asai et al 2003).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Previously, we demonstrated that the ESS3 within the terminal exon of HIV-1 not only inhibits use of the adjacent 3Ј ss but also blocks Rev-mediated export of the unspliced viral RNA to the cytoplasm (Pongoski et al 2002;Asai et al 2003). This block to Rev-mediated export was not due solely to the inhibition of splicing because replacement of ESS3 with high affinity hnRNP A1-binding sites was found to yield a comparable reduction in splicing but did not inhibit RNA transport (Asai et al 2003).…”
Section: Resultsmentioning
confidence: 91%
“…This block to Rev-mediated export was not due solely to the inhibition of splicing because replacement of ESS3 with high affinity hnRNP A1-binding sites was found to yield a comparable reduction in splicing but did not inhibit RNA transport (Asai et al 2003). Consequently, to identify the basis for the ESS3-induced block to unspliced RNA transport, our focus shifted to events other than splicing that are implicated in controlling RNA nuclear/cytoplasmic transport.…”
Section: Resultsmentioning
confidence: 99%
“…The Western Lightning Chemiluminescence Reagent Plus kit (PerkinElmer Life Sciences) was used, according to the manufacturer's instructions. For cell fractionation studies, the nuclear and cytoplasmic fractions were prepared as previously described prior to Western analysis (39). For IRES activity determinations, cells were harvested with passive lysis buffer (Promega, Madison, WI), and 20 g of cellular protein was used to assess IRES activity with the dual-luciferase reporter assay system (Promega) according to the manufactur-er's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Retroviruses use many general SREs to regulate splicing of their RNA (for review, see Stoltzfus and Madsen 2006) and also use RNA elements to regulate nuclear export of unspliced RNA (for reviews, see Pollard and Malim 1998;Cullen 2003). How HIV RNAs balance between the two pathways is not completely clear, but some common elements might serve as a functional bridge between the two pathways by participating in the regulation of both splicing and RNA export (e.g., an ESS recognized by hnRNP A1 [Asai et al 2003] and the Rev response elements [Pongoski et al 2002]). …”
Section: Elements That Regulate Intron Retentionmentioning
confidence: 99%